On the Prospect of Fossil Fuel on Planet Mars - Al Dallal, Shawki (European Journal of Applied Sciences, 2023)
Planet Mars has long been a source of attraction to astronomers and scientists. In 1976, the Viking probes inaugurated the beginning of a new era in human history by searching for primitive lifeforms on Mars. Successive Martian missions have discovered evidence, in the form of dried rivers and lake beds, of the prior abundance of water on the Martian surface leading to conjecture that, millions of years ago, some kind of primeval lifeforms, supported by chemical and biological processes, are at the origin of formation of fossil fuel on planet Mars. One hypothesis even maintains that conditions on Mars, in its early history, resembled, to a major extent, the environment reigning on Earth in its embryonic stage. Petroleum has been the outcome of this natural environment on Earth. It is argued that nascent conditions on Mars developed a fertile environment leading to the formation of fossil fuel. The aim of this paper is to investigate the prospect of such hypothesis, and to examine the likelihood that subterranean resources being extant in Mars in view of the latest data gathered by Martian probes. Analysis shows that kerogen is a viable signature of the potential presence of fossil fuel on Mars, and this result comports with preliminary findings of the Martian Rovers.